The philosophy of animal minds - Lurz, Robert W., 1968- (Cambridge University Press, 2009)
This volume is a collection of fourteen essays by leading philosophers on issues concerning the nature, existence, and our knowledge of animal minds. The nature of animal minds has been a topic of interest to philosophers since the origins of philosophy, and recent years have seen significant philosophical engagement with the subject. However, there is no volume that represents the current state of play in this important and growing field. The purpose of this volume is to highlight the state of the debate. The issues which are covered include whether and to what degree animals think in a language or in iconic structures, possess concepts, are conscious, self-aware, metacognize, attribute states of mind to others, and have emotions, as well as issues pertaining to our knowledge of and the scientific standards for attributing mental states to animals.